Optical intersubband transitions in quantum wires with an applied magnetic field - Ibragimov, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The intersubband optical absorption is investigated in parabolic quantum wires in the presence of a tilted magnetic fields. We show that for increasing magnetic field the intersubband absorption peak is shifted to higher energies and its amplitude is increased, too. In particular, it has been shown that the direction of the magnetic field plays a significant role in the intersubband optical absorption.